Rancang Bangun Robot Electronic Nose untuk mengidentifikasi Gas Menggunakan Multi Layer Perceptron - I Dewa Gede Rai M (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2014)
Research in the field of robotics development equipped with electronic nose is a new challenge. By implementing electronic nose, the robot can identify and mitigate the risks arising from the interaction between humans andharmful gases. This research used robotino that was programmed and equipped with electronic nose to make it more easy and flexible to be controlled by humans to approach the object (toxic gas), as well as designing an artificial intelligence using Multi Layer Perceptron with Error Back Propagation method to gain the weight. The weight that was obtained will be applied to a robot, so by using feed forward process according to these weight, the robot was able to precisely and quickly identify gasses that were obtained from the output of TGS array sensors. Experiment result shows that by training 12 sample data, the robot is able to classify gasoline and alcohol with the accuracy of 100%.